A 150‐year variation of the Kuroshio transport inferred from coral nitrogen isotope signature. (27th June 2016) - Yamazaki, Atsuko; Watanabe, Tsuyoshi; Tsunogai, Urumu; Iwase, Fumihito; Yamano, Hiroya
Abstract: The Kuroshio Current is a major global ocean current that drives the physical ocean‐atmosphere system with heat transport from tropical to temperate zones in the North Pacific Ocean. We reconstructed the variability of the Kuroshio transport over the past 150 years using coral skeletal nitrogen isotopic composition (δ 15 Ncoral ). A 150 year δ 15 Ncoral record (1859–2008 A.D.) is 4 times the length of the observational record (1971 to present) and could provide a direct comparison with global climate change, such as the Pacific Decadal Oscillation (PDO) index and El‐Niño–Southern Oscillation (ENSO), through recent global warming. Coral cores from Porites were collected from Tatsukushi Bay in 2008 on the Pacific coast of Japan, which is located on the northern front of the Kuroshio Current. δ 15 Ncoral was used as a proxy to record the δ 15 N of nitrate (δ 15 Nnitrate ) controlled by the upwelling of subtropical subsurface water (δ 15 Nnitrate ; ~ +2 − +3‰), and δ 15 Ncoral was negatively correlated with observations of the Kuroshio transport ( R  = −0.69, P  < 0.001) and the 2 year lagged PDO index ( R  = −0.63, P  < 0.005) from 1972 to 2007. The 150 year record of δ 15 Ncoral suggested that the Kuroshio transport varied with ~25 year cycle, and the amplitude became more stable, and the volume was intensified through the twentieth century. The Kuroshio transport was intensified by the La Niña state in the early 1900s and by the El Niño‐PDO state after the 1920s. Our results suggested that the Kuroshio transport was influenced by the combined climate modes of ENSO and PDO during the last century. Key Points: We present a 150 year Kuroshio transport variation using new coral δ 15 N proxy Our coral record suggests the acceleration of Kuroshio intensity through the twentieth century We demonstrate the relationships between Kuroshio evolution and ENSO‐PDO states